LITERATURE REVIEW: MITOS LARANGAN KERAMAS TERHADAP PERILAKU PERSONAL HYGIENE SAAT MENSTRUASI DALAM PERSPEKTIF ANTROPOLOGI KESEHATAN - Rahmawati, Windi Chusniah; Fadilla, Asylia Rahma; Amanda, Dian; Azizah, Elisa Lutfiyah Azizah Lutfiyah; Nugroho, Muhammad Ilham; Febiana, Viona Riska Febiana Riska; Pasambe, Yudea (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
Reproductive health includes physical, social, and mental conditions related to the reproductive system and functions, not just freedom from disease and disability. In some regions in Indonesia, there are many myths that are popular in the community, especially regarding menstruation. One myth that is still circulating is the prohibition of shampooing during menstruation. People who believe in this myth are four times more likely to experience personal hygiene problems during menstruation than those who do not believe in it. This article uses the literature review method to compile a health anthropology view of the myth of the prohibition of shampooing during menstruation. The results show that this myth is still believed by many people, even though it is not true. Women still need to maintain personal hygiene including hair during menstruation because the skin becomes oilier and sweatier, increasing the risk of dandruff and other microorganisms. Spreading myths can affect adolescents' personal hygiene. Therefore, efforts are needed to improve adolescents' understanding of hygiene culture and avoid unwarranted beliefs that can negatively affect genitalia health and overall reproductive health by integrating comprehensive health education and utilizing digital technology to access accurate or reliable information.